A polymorphism at the microRNA binding site in the 3' untranslated region of RYR3 is associated with outcome in hepatocellular carcinoma - Zhang, Xiaolan; Guo, Zhanjun; Wu, Xiaoyan; Peng, Chenxing (OncoTargets and therapy, 2015)
MicroRNAs can bind to the 3' untranslated regions (UTRs) of messenger RNAs, where they interfere with the translation of targeting genes, thereby regulating cell differentiation, apoptosis, and tumorigenesis. In this study, three microRNA binding site single nucleotide polymorphisms (SNPs) located in the 3' UTR of RYR3 (rs1044129), C14orf101 (rs4901706), and KIAA0423 (rs1053667) were genotyped to assess their relationships with the risks and outcomes of hepatocellular carcinoma (HCC). The SNPs were genotyped with the ligation detection reaction method. Renilla luciferase reporter assays were used to measure the binding affinity between microRNA 367 and RYR3. Survival curves were calculated using the Kaplan-Meier method, and comparisons between the curves were made using the log-rank test. Multivariate survival analysis was performed using a Cox proportional hazards model. It was found that rs1044129 at the 3' UTR of RYR3 was related to postoperative survival in HCC, with the AA type associated with longer survival times as per the log-rank test. After adjusting with the Cox model, rs104419 was identified as an independent predictor of HCC survival (relative risk: 1.812; 95% confidence interval: 1.026-3.201; P=0.041). Luciferase analysis also indicated the different binding affinities between the SNPs of rs1044129 and microRNA 367. The SNP in the microRNA binding site of RYR3 can be used as a valuable biomarker when predicting HCC outcomes.